2021
DOI: 10.3390/molecules26216560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol Treatment on Human Pancreatic Cancer Cells through Alterations of Bcl-2 Family Members

Abstract: Pancreatic cancers are among of the most lethal types of neoplasms, and are mostly detected at an advanced stage. Conventional treatment methods such as chemotherapy or radiotherapy often do not bring the desired therapeutic effects. For this reason, natural compounds are increasingly being used as adjuvants in cancer therapy. Polyphenolic compounds, including resveratrol, are of particular interest. The aim of this study is to analyze the antiproliferative and pro-apoptotic mechanisms of resveratrol on human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A current report has revealed that normal expression of BAX in tumor cells was related with better consequences, while expression of BCL-2 in cancer cells affected drug resistance. Consequently, it is predicted that changing the expression of these genes will cause apoptosis and inhibit the cancer cells growth [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A current report has revealed that normal expression of BAX in tumor cells was related with better consequences, while expression of BCL-2 in cancer cells affected drug resistance. Consequently, it is predicted that changing the expression of these genes will cause apoptosis and inhibit the cancer cells growth [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Res was also reported to induce the accumulation of cells in the G0/G1 or S phase and reduced the number of cells in the G2/M phase [ 59 , 60 , 61 ]. Our work demonstrates that, in hypoxia, Res alone and in combination with CisPt induces accumulation of A2780 cells in the S phase and decreases the number of cells in the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…For example curcumin has a synergistic effect when administered with gemcitabine [38,39]. Resveratrol induced apoptosis and autophagy in PC by upregulating the apoptotic marker Bax and inhibition of nutrient-deprivation autophagy factor-1 (NAF-1), respectively [40][41][42].…”
Section: Introductionmentioning
confidence: 99%